The Correlation of Parents' Roles on Beginning Reading Ability of Grade 1 Students During Home Learning: Korelasi Peran Orang Tua Terhadap Kemampuan Membaca Permulaan Siswa Kelas 1 Selama Pembelajaran di Rumah - Febyanti Nourma Sari; Kemil Wachidah (Universitas Muhammadiyah Sidoarjo, 2022)
This research is motivated by the fact that in class 1 SDN Candiharjo there are several students who are experiencing problems related to their reading ability. Moreover, the learning process is a lot and is often done at home, due to the conditions during the pandemic which requires him to study at home with his parents. Therefore, the researcher wants to examine whether there is a relationship between the role of parents during the learning process at home with the early reading ability of grade 1 students. So the purpose of this study is to find a correlation between the two. This researcher uses a quantitative correlation research approach. Collecting data in this study used a questionnaire on the role of parents and assessment of the reading ability of grade 1 students. The results of this study indicate that there is a positive correlation between the role of parents on the early reading ability of grade 1 students with very strong significance. Highlights: Parental involvement: The research emphasizes the importance of parental involvement in the learning process at home, specifically focusing on the role of parents in enhancing early reading ability in grade 1 students. Positive correlation: The study establishes a positive correlation between the role of parents and the early reading ability of grade 1 students. This suggests that increased parental involvement positively impacts the students' reading skills. Strong significance: The correlation between the role of parents and early reading ability is found to be highly significant. This indicates a robust relationship between parental involvement and the development of reading skills in grade 1 students. Keywords: reading ability, parents' role, grade 1 students, quantitative correlation research, questionnaire.